Faktor-faktor yang Mempengaruhi Kesuksesan Sistem Informasi Remunerasi pada Fakultas Teknik Universitas Brawijaya Malang) - Afifah, Indah Nurul; Suryadi, Suryadi; Nuh, Mohammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
Universities have implemented many information systems that can facilitate the work of users but need to be considered to address the problems faced. Remuneration Information System at Brawijaya University has often been improved, both from the user side of the application and from the application system itself. The purpose of this study is to find out what factors affect the Net Benefits of Remuneration Information System (Study at the Faculty of Engineering Universitas Brawijaya Malang) using the theory of DeLone &McLean 2003. Hypothesis testing formulated in this study uses Partial Least Squares (PLS). The result of this study is that there are seven factors that affect the net benefits of Remuneration Information System, namely: System Quality against User Satisfaction, Quality of Information against Use, Quality of Information on User Satisfaction, Quality of Service to Use, Quality of Service to User Satisfaction, User Satisfaction against Use, User Satisfaction to Net Benefits. The quality of the System on Remuneration Information System has not been good so its use is still low and the use in remuneration information systems is still low so that the Net Benefit is still low.